APPLICABILITY OF THE KAIZEN PHILOSOPHY IN OPERATIONS MANAGEMENT: a study in an automobile company in the interior of the state of São Paulo - Vergani, Ingrid dos Santos; Casagrande, Diego José (Revista Interface Tecnológica, 2023)
This article aims to demonstrate the importance of applying quality in operations management, emphasizing the Kaizen philosophy. To this end, a case study was carried out in an automobile company in the interior of the state of São Paulo. The meaning of the word Kaizen is linked to continuous improvement. It is essential that employees are prepared to contribute with their ideas for improvement, positively favoring the company’s results. The methodology used in the work was descriptive and quantitative research, through the elaboration of a training applied to the company’s employees who participated in Kaizen. The liabilities seek to assess how employees deal with Kaizen, the degree of knowledge they have about this tool and its applicability. Through the results obtained in the empirical research, it was possible to suggest some improvement alternatives for the use of the Kaizen tool, such as training for better use of the tool and better dissemination of the results obtained through its application.